Occupational Health Problems and Healthcare Seeking Behaviour among Power-loom Workers - Abbas, Md Golam; Jishan, Tawfika Rahman; Yasmin, Shoara; Thamima, Ummay; Islam, Sinthea; Ameen, Muhammad Syeeful; Rahman, Md Shafiur (Eastern Medical College Journal, 2023)
Background: Power-looms sector plays a significant role in the economic growth of Bangladesh. Occupational health problem is a burning issue for developing and developed countries whose economies are dependent on labour-intensive industrial sectors, such as the power-loom sector. Materials &Methods: A cross-sectional study was conducted to assess the occupational health problems and health care seeking behaviour among 332 power-loom workers working in Sirajganj district, Bangladesh through face-to-face interviews by a pretested semi-structured questionnaire. Results: The mean age of the power-loom workers was 31.7±10.4 years and a considerable number of participants (28.9%) had no formal education. Most workers (85.5%) were full-time power-loom workers, which is relevant to factors connected to health concerns and healthcare seeking behaviours. The mean working hours were 12.4±3.1 hours, working days were 6.0±0.3 days and 47.9% of the respondents reported feeling stressed while at work. Most of the power-loom workers (91.9%) were dependent on allopathic treatment. Many of the workers (78.3%) believed that their government did not provide a hospital and that NGOs only operated in a limited capacity (16.3%). It was stated that there was no maternity leave or allowance for the 100% female workforce. Presence of emergency measures was available opined by the half of the workers (49.1%). Lower back pain, neck discomfort, and upper back pain were the three most common musculoskeletal conditions, and they were substantially correlated with worker age and working hours. Conclusion: The study concludes that power-loom workers are prone to develop musculoskeletal problems and strategies need to be developed to limit the problem and to promote their health. Eastern Med Coll J. July 2023; 8 (2):54-60